The discovery of pulsars - Bell Burnel, Jocelyn (Cadernos de Astronomia, 2024)
This text was extracted from the lecture given on February 10, 2023 by the author at the second edition of the event As Astrocientistas: Brazilian Meeting of Girls and Women of Astrophysics, Cosmology and Gravitation.